Key cell signaling pathways modulated by zerumbone: Role in the prevention and treatment of cancer - Prasannan, R.; Kalesh, K.; Shanmugam, M.; Nachiyappan, A.; Ramachandran, L.; Nguyen, A.; Kumar, Alan Prem; Lakshmanan, M.; Ahn, K.; Gautam, S. (Elsevier, 2012)
Phytochemicals and their synthetic derivatives are making a significant contribution in modern drug discovery programs by targeting several human diseases, including cancer. Most of these natural compounds are often multitargeted in nature, which is generally a very desirable property for cancer therapy, as carcinomas typically involve dysregulation of multiple genes and associated cell-signaling pathways at various stages of initiation, progression and metastasis. Additionally, these natural agents generally have lower side-effects, are readily available and hence are cost effective. One such natural compound is zerumbone, a cyclic eleven-membered sesquiterpene, isolated from the tropical plant Zingiber zerumbet Smith that has attracted great attention recently for its potent anticancer activities in several tumor models. This review summarizes the data based on various in vitro and in vivo studies related to the effects of zerumbone on numerous pivotal molecular targets in cancer and its reported chemopreventive/therapeutic effects in different models of cancer.